Temporomandibular Joint Arthritis Resembling Bifid Condyle - A CBCT Analysis of 2 Cases - S Jayachandran; Priyanka Khobre; K Sarala (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2016)
Rheumatoid arthritis is an autoimmune disorder which can cause temporomandibular joint involvement with clinical symptoms such as pain, swelling, crepitation and movement impairment. Surface erosion is one of the radiologic feature of rheumatoid arthritis and if it is involving carter of the condylar surface, it can be misdiagnosed for the bifid condyle. Here we report two cases of rheumatoid arthritis with temporomandibular joint involvement where cone beam computed tomography appearance is mimicking bifid condyle because of erosion of the condylar surface.